2008
DOI: 10.1161/circulationaha.108.790162
|View full text |Cite
|
Sign up to set email alerts
|

Milrinone Use Is Associated With Postoperative Atrial Fibrillation After Cardiac Surgery

Abstract: Background-Postoperative atrial fibrillation (AF), a frequent complication after cardiac surgery, causes morbidity and prolongs hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 34 publications
4
54
0
1
Order By: Relevance
“…28,29,30,31,32 Andrews et al showed that the incidence of POAF decreased from 34% to 8, 7% in patients received beta-blockers. In another meta-analysis of Kowey et al, the decrease in incidence of AF was from 20% to 8, 7%.…”
Section: Discussionmentioning
confidence: 99%
“…28,29,30,31,32 Andrews et al showed that the incidence of POAF decreased from 34% to 8, 7% in patients received beta-blockers. In another meta-analysis of Kowey et al, the decrease in incidence of AF was from 20% to 8, 7%.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that vasopressor therapy, and not inotropic therapy, was an independent predictor is also somewhat contradictory. The inotropic agent used in this study was milrinone, which was demonstrated to be a strong independent risk factor of postoperative AF following cardiac surgery [25]. The vasopressor used in this study was norepinephrine in doses not exceeding 0.3 mg kg À1 min À1 .…”
Section: Discussionmentioning
confidence: 99%
“…In multivariable logistic regression, age (p < 0.001), ejection fraction (p ¼ 0.02), and milrinone use (odds ratio, 4.86; 95% confidence interval, 2.31-10.25; p < 0.001) independently predicted postoperative AF. Although the use of milrinone was not directly linked to mortality, patients who developed AF stayed in the hospital longer (p < 0.001) and were more likely to die (p ¼ 0.02) [13]. However, atrial fibrillation is very rare in children, and in particular its occurrence has not been associated with the use of milrinone in children.…”
Section: Lcos After Congenital Heart Surgerymentioning
confidence: 97%
“…Of interest, in a recent study by Fleming et al the use of milrinone was associated with an increased risk of postoperative atrial fibrillation after cardiac surgery in adults (58.2% versus 26.1% in nonusers; p < 0.001) [13]. In multivariable logistic regression, age (p < 0.001), ejection fraction (p ¼ 0.02), and milrinone use (odds ratio, 4.86; 95% confidence interval, 2.31-10.25; p < 0.001) independently predicted postoperative AF.…”
Section: Lcos After Congenital Heart Surgerymentioning
confidence: 99%